2011
DOI: 10.1002/ajh.22095
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of monoclonal gammopathy of undetermined significance in an elderly urban Korean population

Abstract: Research on the epidemiology of monoclonal gammopathy of undetermined significance (MGUS) is limited in Korea. The aim of this study was to determine the prevalence and characteristics of MGUS in an elderly urban Korean population. A random sample of 1118 Korean elders was selected from residents aged 65 years or older living in Seongnam, Korea 1 year from August 2005. We obtained plasma samples remaining after scheduled tests for the Korean Longitudinal Study on Health and Aging. The mean age of the study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Our findings are consistent with older studies showing that Asians have a fivefold lower incidence of multiple myeloma compared with whites, 3 and are consistent with prior MGUS prevalence studies in Thailand (2.3%; 95% CI, 1.1%-4.6%), 4 Korea (3.3%; 95% CI, 1.0%-4.2%), 5 and Japan (2.1%; 95% CI, 1.9%-2.2%). 6 In the Olmsted County study conducted by the Mayo Clinic, the prevalence of MGUS among 50-to 59-year-old and 60-to 69-year-old whites was 1.6% and 3.0%, respectively.…”
supporting
confidence: 92%
“…Our findings are consistent with older studies showing that Asians have a fivefold lower incidence of multiple myeloma compared with whites, 3 and are consistent with prior MGUS prevalence studies in Thailand (2.3%; 95% CI, 1.1%-4.6%), 4 Korea (3.3%; 95% CI, 1.0%-4.2%), 5 and Japan (2.1%; 95% CI, 1.9%-2.2%). 6 In the Olmsted County study conducted by the Mayo Clinic, the prevalence of MGUS among 50-to 59-year-old and 60-to 69-year-old whites was 1.6% and 3.0%, respectively.…”
supporting
confidence: 92%
“…To date, the MGUS prevalence in Koreans has been determined only in elderly people >65 years [3]. In the present study, the prevalence of MGUS in participants >60 years was 3.80% which was similar to those obtained from elderly Korean male aged over 65 years (3.8%) [3]. …”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that MGUS prevalence values in Korean men in their 40 (0.00%), 50 (1.63%), and >60 years of age (3.80%) were similar to MGUS values for Japanese males in their 40 (1.2%), 50 (2.7%), and >60 years of age (4.3%) and Chinese men 50–65 years (1.2%) [8, 9]. To date, the MGUS prevalence in Koreans has been determined only in elderly people >65 years [3]. In the present study, the prevalence of MGUS in participants >60 years was 3.80% which was similar to those obtained from elderly Korean male aged over 65 years (3.8%) [3].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…One more thing we should consider is the incidence of monoclonal gammopathy of undetermined significance (MGUS) among Asian countries. Surprisingly, the incidence of MGUS is almost equivalent or only slightly lower than what has been reported in Western countries, although the number of studies is very limited . Considering that MM is almost always preceded by MGUS, the reported incidence of MGUS in Asian countries would lead us to expect that the incidence of MM will further increase in the near future.…”
Section: Discussionmentioning
confidence: 89%